Soil erosion in East Africa: an interdisciplinary approach to realising pastoral land management change. (3rd December 2018) - Blake, William H; Rabinovich, Anna; Wynants, Maarten; Kelly, Claire; Nasseri, Mona; Ngondya, Issakwisa; Patrick, Aloyce; Mtei, Kelvin; Munishi, Linus; Boeckx, Pascal; Navas, Ana; Smith, Hugh G; et al.
Abstract: Implementation of socially acceptable and environmentally desirable solutions to soil erosion challenges is often limited by (1) fundamental gaps between the evidence bases of different disciplines and (2) an implementation gap between science-based recommendations, policy makers and practitioners. We present an integrated, interdisciplinary approach to support co-design of land management policy tailored to the needs of specific communities and places in degraded pastoral land in the East African Rift System. In a northern Tanzanian case study site, hydrological and sedimentary evidence shows that, over the past two decades, severe drought and increased livestock have reduced grass cover, leading to surface crusting, loss of soil aggregate stability, and lower infiltration capacity. Infiltration excess overland flow has driven (a) sheet wash erosion, (b) incision along convergence pathways and livestock tracks, and (c) gully development, leading to increased hydrological connectivity. Stakeholder interviews in associated sedenterising Maasai communities identified significant barriers to adoption of soil conservation measures, despite local awareness of problems. Barriers were rooted in specific pathways of vulnerability, such as a strong cattle-based cultural identity, weak governance structures, and a lack of resources and motivation for community action to protect shared land. At the same time, opportunities for overcoming such barriers exist, through openness to change and appetite for education and participatory decision-making. Guided by specialist knowledge from natural and social sciences, we used a participatory approach that enabled practitioners to start co-designing potential solutions, increasing their sense of efficacy and willingness to change practice. This approach, tested in East Africa, provides a valuable conceptual model around which other soil erosion challenges in the Global South might be addressed.